The Use of Good Governance of Educational Administrators in School Network 45-46 Mongchok District Bangkok Metropolis - หล้าพวงคำ จิตตราพร; น้อยมณี นิวัตต์; สุวรรณธารา ภูวนัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research were (1) to study the level of use of good governance principles by educational institution administrators; School Network Group 45-46, Nong Chok District Office Bangkok and (2) to comparison Use of good governance principles by educational institution administrators School Network Group 45-46, Nong Chok District Office Bangkok. Classified by gender, educational qualifications, age, work experience. Classified by gender, educational qualifications, age, work experience. The sample group used in this research was government teachers, school network groups 45-46, Nong Chok District Office Bangkok. Academic year 2023, a total of 242 people were obtained using the sample size determination method. According to the sample size table of Krejci and Morgan. Then randomize in a stratified way. Then use a simple merging method. The tool used to collect data was a 5-level rating scale questionnaire with a reliability value for the entire version equal to .974. Data were analyzed by finding frequencies, percentages, means, and standard deviations. Differences between samples were also tested. T-value and one-way analysis of variance. When a statistically significant difference was found, a test was performed to compare the difference in mean scores by pair. Using Scheffe’s difference detection method. The results were 1) The Use of good governance principles by educational institution administrators School Network Group 45-46, Nong Chok District Office Bangkok Overall it is at a high level. When considering each aspect, it was found that the first average was Rule of law Next is the aspect of moral principles. And the last ranking is Principles of transparency. Comparative results of the use of good governance principles by educational institution administrators. School Network Group 45-46, Nong Chok District Office Bangkok classified by gender, educational background, found that both overall and each aspect The difference is not statistically significant. And when classified by age and work experience, it was found that both overall and each aspect They are significantly different at the .05 level.